2002
DOI: 10.1121/1.1506694
|View full text |Cite
|
Sign up to set email alerts
|

Computational aeroacoustics of phonation, Part II: Effects of flow parameters and ventricular folds

Abstract: The results are described of the second part of an ongoing study aimed at performing direct numerical simulations of translaryngeal flows during phonation. The use of accurate numerical schemes allows the radiated sound to be calculated directly, without the need for acoustic analogy models. The goal is to develop a better understanding of this class of flow, and of the basic sound generation mechanisms involved in phonation. In the present study, the effects of subglottal pressure and of glottal oscillation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 4 publications
2
61
0
1
Order By: Relevance
“…The unsteady glottal flow rate has a direct relation to the sound quality Zhang et al, 2002). Two additional quantities: The root-mean-square fluctuation of the flow rate Q 0 rms and the root-mean-square fluctuation of the time-rate change of the flow rate _ Q rms , are computed to further investigate the impact of tension imbalance on voice quality; Q 0 rms indicates the intensity of glottal flow rate fluctuations and further connects to the intensity of VF vibrations, and _ Q rms is directly related to the monopole sound strength.…”
Section: Effect Of Vf Tension Asymmetry On Phonationmentioning
confidence: 99%
See 1 more Smart Citation
“…The unsteady glottal flow rate has a direct relation to the sound quality Zhang et al, 2002). Two additional quantities: The root-mean-square fluctuation of the flow rate Q 0 rms and the root-mean-square fluctuation of the time-rate change of the flow rate _ Q rms , are computed to further investigate the impact of tension imbalance on voice quality; Q 0 rms indicates the intensity of glottal flow rate fluctuations and further connects to the intensity of VF vibrations, and _ Q rms is directly related to the monopole sound strength.…”
Section: Effect Of Vf Tension Asymmetry On Phonationmentioning
confidence: 99%
“…With the remarkable advances in computational power as well as computational modeling techniques in the last several decades, continuum based models of phonation have undergone rapid improvement. Initial attempts were mostly with two-dimensional (2D) models (Zhao et al, 2001;Zhao et al, 2002;Zhang et al, 2002;Alipour and Scherer 2004). Furthermore, immersed boundary method based solvers have also found an increased use in these models (Duncan et al, 2006;Luo et al, 2008;Luo et al, 2009;Zheng et al, 2009) due to their inherent ease of application to complex biological problems with moving/deforming boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the models of Zhang et al [12] and Scherer et al [14], the larynx shape function of a model with FVFs is written as…”
Section: Appendixmentioning
confidence: 99%
“…Zhang et al [12] numerically investigated the effect of the FVFs on the speech production process on the basis of the axisymmetric forced vibrating TVF model. They reported that the impingement of the glottal jet on the FVFs causes the generation of additional sources in speech waves.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the models of Zhang et al [12] and Scherer et al [13], the glottal shape function is written as…”
Section: Rigid Glottal Modelmentioning
confidence: 99%